Validation of integrated pest management strategy against coconut rhinoceros beetle, Oryctes rhinoceros L. (Scarabaeidae: Coleoptera) - K. Rajamanickam, T. Srinivasan,; H.P. Maheswarappa, Chandrika Mohan, (Journal of Plantation Crops, 2018)
Juvenile palms in the age group of one to six years are prone to damage in the crown by rhinoceros beetle. Damage by the beetle results in ‘V’ shaped cuts in the leaf lamina and repeated attacks by the pest results in reduced leaf area for photosynthesis. Integrated pest management modules were developed for the management of coconut rhinoceros beetles and were validated under field conditions. Validation studies undertaken in three locations revealed that IPM practices including setting up of Rhinolure (PCI ) pheromone traps @ one per ha, field release of Oryctes rhinoceros virus suspension treated adults @ 15 per ha, placement of naphthalene balls @ 10 to 12 g per palm in the innermost leaf axil once in 45 days and application of green muscardine fungi, Metarhizium anisopliae to the manure pits during rainy seasons resulted in reduction in leaf and spindle damage to less than 10 per cent in all the locations tested. Site occupancy studies revealed the presence of virus infected O. rhinoceros and green muscardine fungus infected grubs in the manure pits adjacent to the experimental plots.